The use of Pb isotope ratios determined by magnetic sector ICP-MS for tracing Pb pollution in marine sediments near Casey Station, East Antarctica - Ashley Townsend; I Snape (2002)
Magnetic sector inductively coupled plasma mass spectrometry (ICP-SMS) was used to measure lead concentrations and isotope ratios in marine sediments and other samples collected from near the Australian Antarctic Station Casey. Precisions obtained from the repetitive analysis of a standard Broken Hill Pb sample at a concentration of ∼40 ng g-1 in solution were <±0.2% for ratios involving 204Pb, and <±0.1% for those referenced to 206Pb or 207Pb (n = 12 replicates over 2 days, values as 1s). Ratios were accurate to within ∼±0.1% for the analysis of this standard sample. Comparative measurements between ICP-SMS and TIMS had typical differences in values of <0.4% for contaminated samples, irrespective of ratio. For marine sediment samples with Pb concentrations in the sample digest of >10 ng g-1, instrumental capability was characterised by isotopic precisions ranging from 0.1-0.5% (1s) for ratios involving 204Pb, and <0.25% (1s) for ratios with 206Pb or 207Pb as the basis (typically found from triplicate analyses). For sediments of low Pb concentration (<10 ng g-1 in the sample digest), isotope ratios to 204Pb were found to be limited by instrument counting statistics when using standard ICP-SMS. To help overcome this problem, Pb isotope ratios for these samples were measured with a capacitive decoupling Pt guard electrode employed, offering considerable signal enhancement (5-10x). These natural background sediments were found to display typical Pb isotope ratios of 40.5, 15.5, 18.6 and 1.19 for 208Pb/204Pb, 207Pb/204Pb, 206Pb/204Pb and 206Pb/207Pb. For comparison, the most contaminated samples had Pb isotope ratios of approximately 36.2, 15.4, 16.4 and 1.06 for 208Pb/204Pb, 207Pb/204Pb, 206Pb/204Pb and 206Pb/207Pb, respectively. Evidence of simple two component mixing between anthropogenic and natural geogenic Pb was found near Casey Station. Runoff from the Thala Valley tip site, adjacent to the bay, was identified as a clear source of Pb pollution, with impacted sediments displaying an ...